The Urgency of Criminalizing Femicide as a Specific Crime within the Indonesian Legal System - Novia Rahmadani; M. Rizki Yudha Prawira (Jurnal Ilmiah Dunia Hukum, 2025)
This research discusses femicide, which is the most extreme form of gender-based violence, but the Indonesian legal framework, particularly the Criminal Code (KUHP) and the Law on Sexual Violence Crimes (UU TPKS), does not explicitly recognize gender-motivated murder of women. As a result, femicide cases continue to be prosecuted under general homicide provisions without acknowledging discriminatory motives, leading to inadequate legal protection and disproportional sentencing. This research aims to analyze the urgency of criminalizing femicide as a special offense and to formulate an ideal legal concept for its regulation within the Indonesian criminal justice system. Using a normative juridical method supported by statutory, comparative, and conceptual approaches, this study examines national legal norms, international human rights instruments, and comparative legislation from Argentina, Chile, and Mexico. The findings show that a specific femicide offense is essential to fill normative gaps, incorporate gender-based motives as an aggravating factor, and strengthen state obligations under Convention on the Elimination of All Forms of Discrimination Against Women, the Belém do Pará Convention, and other global standards. The study concludes that Indonesia requires a dedicated femicide law based on lex specialis principles, gender-sensitive investigation and adjudication mechanisms, and integrated victim-protection measures to ensure a more just, responsive, and gender-equitable criminal law system.